Comparison of Life Skills between Students Who Participate in Sports Extracurriculars and Non-Sports Extracurriculars at SMPN 1 Banyakan Kediri - Moch. Haris Arsada Laroibafi; Rizki Burstiando; Muhammad Yanuar Rizky (CV. Nusantara Sporta, 2024)
This research evaluates the comparison of life skills between students who take part in sports and non-sports extracurricular activities at SMPN 1 Banyakan Kediri. The method used is descriptive quantitative with surveys and questionnaires as instruments. The sample consisted of 60 students, evenly divided between sports and non-sports extracurricular activities. The research results show that students who are involved in extracurricular sports have better life skills compared to non-sports students. The life skills categories assessed were Low (0% vs 10%), Medium (30% vs 30%), High (36.67% vs 16.67%), and Very High (23.33% vs 43.33% ). The highest percentage was found in the Very High category for non-sports extracurriculars (43.33%). The statistical test results show a tcount value of 38.262 < ttable 1.672 and a sig value of 0.667 > 0.05, which indicates there is no statistically significant difference between the two groups.